Vaccination associated with gross domestic product and fewer deaths in countries and regions: A verification study. Issue 4 (28th January 2022) - Wang, Lin-Yen; Chien, Tsair-Wei; Lin, Ju-Kuo; Chou, Willy
Abstract: Background: Vaccination can have a substantial impact on mitigating COVID-19 outbreaks. However, the vaccine rollout rates associated with the gross domestic product (GDP) and few deaths are required for verification. Three hypotheses were made: the inflection point (IP) days on the cumulative number of confirmed cases (CNCCs) in 2021 are improved (i.e., shorter than 2021); the vaccinations are associated with national GDP and fewer deaths; and the association is weak between vaccinations and CNCC IP based on the argument that vaccinations are limited to protection against milder infection. Methods: The corresponding CNCCs and deaths were downloaded from the GitHub website. Four variables, including IP days on CNCCs and deaths, GDP per capita, and vaccine doses administered per 100 people (VD100) in countries/regions, were collected. Correlation coefficients (CCs) between variables were computed to verify the association with vaccination rates. Four tasks were achieved: determining IP days for each country/region; drawing forest plots to identify the improvement in 2021; using a pyramid plot to identify the improvement in US states; and applying the Kano diagram to verify the three hypotheses mentioned above. Results: We observed that the IP days on CNCCs in 2021 were shorter than those in 2021 among continents and US states; the CCs were 0.66 ( t = 12.21, P < .01) and −0.15 ( t = 2.11, P < .01) using the paired variables of [VD100, GDP] and [VD100, deaths IP], respectively; and the CC between CNCC IP and deaths IP was 0.73 ( t = 14.84, P < .01), but a weak association with CC = −0.01 existed between CNCC IP and VD100. Conclusion: Our results indicate that vaccination has a significant effect on mitigating COVID-19 outbreaks, even with limited protection against infection. Continued compliance with nonpharmaceutical interventions is essential to the fight against COVID-19 in the future. Abstract : Supplemental Digital Content is available in the text